Randomized Trial on Echocardiography-Guided Ductus Arteriosus Treatment to Reduce Necrotizing Enterocolitis - Bravo, María Carmen; Sánchez-Salmador, Rebeca; Moral-Pumarega, María Teresa; López-Azorín, Manuela; Mosqueda-Peña, Rocío; Dorronsoro, Izaskun; Cabañas, Fernando; Pellicer, Adelina (Frontiers in Pediatrics, 2022)
Objective Patent ductus arteriosus (PDA) approach remains controversial. We aim to evaluate whether echocardiography-guided (EchoG) PDA closure (to reduce drug exposure) and 24-h continuous ibuprofen infusion (24 h-IB) (to reduce peak concentration), compared with EchoG PDA closure plus conventional bolus (bolus-IB), reduces severe bowel adverse event rate in preterm infants with hemodynamically significant (hs) PDA. Study Design The study design is a multicenter, blinded, randomized controlled trial. Infants with <28 weeks of gestation underwent routine echocardiographic assessment (18–72 h of birth); infants with 28–33 weeks were screened only in cases where PDA was clinically suspected. HsPDA was considered if ductal diameter >1.5 mm and indicators of pulmonary overflow, systemic hypoperfusion, or both were present. Pharmacodynamic effect of CYP450 genotypes was also analyzed. Results One hundred forty-six infants [median gestational age 26 (25–28) weeks; median birth weight 881 (704–1,100) g] were randomized to 24 h-IB (n = 70) or bolus-IB (n = 76) study group at 86 (58–140) h from birth. Groups were comparable regarding perinatal and neonatal clinical data, but higher prevalence of male sex in the bolus-IB group was found. Neither severe bowel adverse event rate [10% (24 h-IB) and 2.6% (bolus-IB), p = 0.1] nor ductal closure rate was different between the study groups. Postnatal age and peripheral SaO2 at treatment start and pulmonary hemorrhage were associated with severe bowel events, independent of treatment group allocation. CYP2C8 genetic polymorphisms were associated with ibuprofen efficacy (p = 0.03). Conclusions Ibuprofen intravenous continuous infusion compared with bolus infusion in preterm infants with hsPDA shows similar rates of success and does not reduce the prevalence of severe bowel events.